Boraginaceae endémicas del Perú - León, Blanca (2006)
The Boraginaceae are represented in Peru by 16 genera and 136 species (Brako & Zarucchi, 1993), mostly shrubs and herbs. Here we recognize 33 endemic species in nine genera, Heliotropium being the most important. Endemic Boraginaceae grow mainly in the Desert Shrubland, Subtropical Costal Desert and Mesoandean regions, between 300 and 4000 m elevation. We applied IUCN categories and criteria to nine endemic species. None of the species have been collected within Peru’s protected area system.